Brain Gym Exercise Give Benefit to Improve Cognitive Function among Elderly: A Systematic Review - Lina, Ratu Karel; Kurniawan, Ganesa Puput Dinda (jitek, 2022)
Being elderly is potentially risk for the emerging of progressive neurodegenerative syndrome, including cognitive impairment. Various efforts have been made to minimize the negative impact. Brain gym is an alternative intervention that is widely used. A series of motion between the legs and hands employed to stimulate the brain to remain optimal. This study aims to determine whether brain gym exercise is beneficial for cognitive improvement among elderly in Indonesia. The systematic literature review was carried out from 28 May 2020 – 05 June 2020 at Semantic Scholar, Google Scholar, Garba Rujukan Digital (Garuda). Searching process employed keywords compiled using PICOS (Population, Intervention, Comparison and Outcomes) method and applied a filtering of articles using clinical trial or randomized controlled trial design, published in the last five years, and free/open access literature. There are 5 articles that meet the inclusion criteria: sample age 60 years and over, type of brain gym intervention, and focus on assessing cognitive function using the Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment Indonesian Version (MoCA-Ina. Overall, the result shows in participants (n=211) experienced a significant increase in cognitive function (p<0.05). Indeed, additional outcomes were found, namely a decrease in stress levels and an increase in physical activity function.